2020
DOI: 10.1136/neurintsurg-2020-016794
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke in COVID-19-positive patients: an overview of SARS-CoV-2 and thrombotic mechanisms for the neurointerventionalist

Abstract: Coronavirus disease 2019 (COVID-19) results from infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It was first reported in Wuhan, China in patients suffering from severe pneumonia and acute respiratory distress syndrome and has now grown into the first pandemic in over 100 years. Patients infected with SARS-CoV-2 develop arterial thrombosis including stroke, myocardial infarction and peripheral arterial thrombosis, all of which result in poor outcomes despite maximal medical, endovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 58 publications
1
79
0
3
Order By: Relevance
“…Therefore, the prognostic value of D-dimer in COVID-19 could differ for COVID-19 patients presenting with AIS, in whom D-dimer levels may be independently elevated. Our study confirmed that D-dimer levels at admission were elevated among COVID-19 patients [0.95 (0.56-1.83) µg/ml FEU] beyond normal range (<0.5 µg/ml FEU) and greater elevations were observed among COVID-19 patients presenting with AIS [1.42 (0.76-3.96) µg/ml FEU] (15,16).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the prognostic value of D-dimer in COVID-19 could differ for COVID-19 patients presenting with AIS, in whom D-dimer levels may be independently elevated. Our study confirmed that D-dimer levels at admission were elevated among COVID-19 patients [0.95 (0.56-1.83) µg/ml FEU] beyond normal range (<0.5 µg/ml FEU) and greater elevations were observed among COVID-19 patients presenting with AIS [1.42 (0.76-3.96) µg/ml FEU] (15,16).…”
Section: Discussionsupporting
confidence: 83%
“…This agrees with previous studies in which COVID-19 was identified as an independent risk factor for stroke. 18,19 The varied multisystemic manifestations of our patients may be related to the wide distribution of the preferred SARS-CoV-2 host receptor, angiotensin-converting enzyme † Based on WHO definition of severity 1 : mild, symptomatic patients with no evidence of viral pneumonia or hypoxia; moderate, SpO2 $ 90%, fever, cough, dyspnea, fast breathing (clinical signs of pneumonia) but no signs of severe pneumonia; severe, SpO2 , 90%, adolescent or adult with clinical signs of pneumonia (fever, cough, dyspnea, fast breathing), severe respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…The well-accepted mechanism of thrombosis due to COVID-19 starts with the innate immune system activation to fight against SARS-CoV-2 invasion. Several factors are involved in the activation of the contact pathway of coagulation, including, innate immune cells, platelets, endothelial cells, intravascular tissue factor, and neutrophil release of extracellular traps ( 88 ). Thus, a reduced blood/oxygen supply to the inner ear can enhance drug ototoxicity ( 89 ).…”
Section: Risk Factors That Exacerbate Ototoxicitymentioning
confidence: 99%